COMPARATIVE STUDY OF ENGLISH AND UZBEK LEGAL TERMINOLOGY - Rakhmonova, Sarvinoz (Oriental Journal of Education, 2026)
Legal terminology is a specialized vocabulary used in laws, court procedures, legal documents, and official communication, characterized by precision, clarity, and unambiguous meaning. It reflects the historical, cultural, and political context of a legal system and is essential for accurate interpretation, translation, and legal practice. Legal terms can be classified into single-word terms, compound terms, and fixed multi-word phrases, each functioning as an indivisible legal unit. Comparative analysis of English and Uzbek legal terminology highlights structural differences. English, influenced by the common law tradition, favors compounds and fixed phrases, allowing complex legal concepts to be expressed concisely. Uzbek, shaped by the civil law system and the analytical nature of the language, predominantly uses multi-word descriptive constructions. Understanding these structural and functional distinctions is crucial for legal translation, cross-cultural communication, and ensuring clarity and certainty in legal texts. The study of legal terminology enables precise expression and consistent interpretation within and across legal systems.